Effects of water properties and soil texture on the growth of a mangrove palm; Nypa fruticans on carey Island, Malaysia - Zakaria, R.M.; Aslezaeim, N.; Sofawi, A.B. (Pakistan Botanical Society, 2017)
Nypa fructicans is a major species of mangrove palm on Carey Island, Malaysia. The main objective of this study is to determine the effects of water properties on the growth of Nypa fruticans. Plant growth measurements and water analyses were carried out in six plots for 16 months. The life stages of Nypa fruticans were divided into seedlings, juveniles, adults and matures, based on the number of leaves. Leaf production of juvenile and mature trees showed negative correlation with salinity. Leaf production of seedlings was affected negatively only by heavy metal of Arsenic (As). Calcium (Ca) in the water had a strong positive effect on the new leaf production of juveniles and on the spear elongation of matures, and Iron (Fe) had a negative effect on the leaf elongation of adults. Similarly, spear elongation of juvenile trees was positively correlated to nitrate (NO3-). Silty clay texture provides the best condition for the growth of Nypa fruticans. The growth of Nypa fruticans was most significantly affected by water parameters in the early life stages.